1980
DOI: 10.1677/joe.0.0850237
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Triglycylvasopressin to Lysine-Vasopressin in Man

Abstract: The concentrations in plasma of triglycl-8-lysine-vasopressin (TGLVP), determined by radioimmunoassay, and lysine-vasopressin, determined by bioassay, have been monitored in five subjects after intravenous (7.5 micron/kg) or intranasal (5 mg) administration of TGLVP. The level of excretion in urine was also measured. The TGLVP concentration in plasma fell rapidly after the intravenous injection, the mean half-time of disappearance being 24.2 +/- 1.9 (S.E.M.) min (d.f. 4). Biologically active lysine-vasopressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 9 publications
1
33
0
2
Order By: Relevance
“…In the first human study with terlipressin in five healthy subjects and in two early rat studies a decrease in diuresis was observed after terlipressin; however, these findings were never explored further (3,10,17). This lack of interest in antidiuresis was probably because people focused on the effects on bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In the first human study with terlipressin in five healthy subjects and in two early rat studies a decrease in diuresis was observed after terlipressin; however, these findings were never explored further (3,10,17). This lack of interest in antidiuresis was probably because people focused on the effects on bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Lysine-vasopressin was determined (as described by Forsling, Aziz, Miller, Davies & Donovan, 1980) by radioimmunoassay using plasma extracted with Fuller's earth (Skowsky, Rosenbloom & Fisher, 1974). Synthetic lysine-vasopressin (Ferring, Malmo) was used as standard and for preparation of labelled peptide by the lactoperoxidase method.…”
Section: Blood Collectionmentioning
confidence: 99%
“…Once formed, lysine-vasopressin is eliminated by plasma peptidase losing its vasopressinergic activity. 36,37 There is a biphasic decline in plasma terlipressin concentration, with an elimination half-life of 50 minutes. Terlipressin administration results in a marked increase in plasma concentrations of lysine-vasopressin, which peaks at 60-120 minutes, and remains elevated for at least 180-240 minutes.…”
Section: Discussionmentioning
confidence: 99%